Investigation into eradication of African swine fever in domestic pigs from a previous outbreak (2016/17) area of South Africa. (December 2020) - Janse van Rensburg, Leana; Penrith, Mary-Louise; van Heerden, Juanita; Heath, Livio; Etter, Eric M.C.
Abstract: A serological survey was conducted to evaluate the eradication of African swine fever (ASF) infection eighteen months after clinical surveillance and selective culling had been completed during domestic cycle outbreaks in parts of South Africa in 2016/17. Three hundred and twenty-two serum samples from 85 pig keepers were collected in the study area and tested for the presence of antibodies against the ASF virus (ASFV). None of the samples contained detectable levels of antibodies against ASFV. These results together with the findings from clinical surveillance following culling activities suggest that the disease had been eradicated from the domestic pig population in this area following the outbreaks. Questionnaire responses from the pig keepers in this area highlighted the need to implement basic biosecurity measures in smallholder pig keepers to prevent outbreaks of ASF in South Africa. Highlights: ASF outbreaks in an area were controlled with selective culling in South Africa. Clinical surveillance and a sero-survey suggests ASF was eradicated in area. Basic biosecurity measures are needed for smallholder pig keepers to prevent ASF. Investigation into possible wildlife ASF sylvatic cycle in the area is recommended.